2013
DOI: 10.1063/1.4775759
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic magnetic structuring of a spin-wave waveguide by ion implantation in a Ni81Fe19 layer

Abstract: We investigate the spin-wave excitation in microscopic waveguides fabricated by localized Cr + ion implantation in a ferromagnetic Ni 81 Fe 19 film. We demonstrate that spin-wave waveguides can be conveniently made by this technique. The magnetic patterning technique yields an increased damping and a reduction in saturation magnetization in the implanted regions that can be extracted from Brillouin light scattering measurements of the spin-wave excitation spectra. Furthermore, the waveguide performance as well… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, the same approach can be adapted to ferromagnetic insulators, such as yttrium iron garnets, where the damping of the magnetization dynamics is greatly reduced and therefore the spin-wave propagation distance is significantly increased. Another approach to reduce the currents required to magnetize the spin-wave waveguide perpendicular to the transport direction is to use ion implantation to imprint waveguides into paramagnetic or ferromagnetic films 24,25 . In such waveguides the shape anisotropy is strongly reduced due to the surrounding ferro-or paramagnetic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the same approach can be adapted to ferromagnetic insulators, such as yttrium iron garnets, where the damping of the magnetization dynamics is greatly reduced and therefore the spin-wave propagation distance is significantly increased. Another approach to reduce the currents required to magnetize the spin-wave waveguide perpendicular to the transport direction is to use ion implantation to imprint waveguides into paramagnetic or ferromagnetic films 24,25 . In such waveguides the shape anisotropy is strongly reduced due to the surrounding ferro-or paramagnetic environment.…”
Section: Discussionmentioning
confidence: 99%
“…In this study the implantation of Cr + ions was used to achieve a periodic modulation of the saturation magnetization in a Ni 81 Fe 19 stripe without actually changing the topography, i.e., without altering the thickness of the magnetic material [89,90]. In a magnonic crystal the chosen periodicity-1 µm in the actual case-defines the Bragg condition and, thus, the position of the resulting band gaps in terms of the wave vector.…”
Section: Examplesmentioning
confidence: 99%
“…The spin-wave dispersion relation depends on many parameters, such as the geometry of the spin-wave waveguide (film thickness and waveguide width), external magnetic field H ext , and saturation magnetization M S . In fact, all of these parameters have already been used to fabricate magnonic crystals [6][7][8]12,13,[18][19][20] : arrays of metallic stripes, etched grooves or antidots, biasing magnetic field or periodic variation of the saturation magnetization using ion implantation.However, all available methods for the fabrication of such spintronic devices result in spatially constant magnetic materials. J. Topp et al have shown that the parameters of magnetic materials can be changed locally after the rather time-consuming fabrication of the spintronic device 21 -but the functionality of the device stays the same.…”
mentioning
confidence: 99%
“…Structuring has been used to control mechanical 10 , optical 11 , and even magnetic properties 12,13 . Periodic variation of the magnetic material's parameters allows the realization of magnonic crystals with novel properties not found in the unstructured material.…”
mentioning
confidence: 99%